2022
DOI: 10.4081/ejh.2022.3529
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-resistant triple-negative breast cancer cell-derived exosomal lncRNA LINC00667 reduces the chemosensitivity of breast cancer cells to docetaxel <em>via</em> targeting miR-200b-3p/Bcl-2 axis

Abstract: Development of docetaxel (TXT) resistance is a major obstacle for triple-negative breast cancer (TNBC) treatment. Additionally, chemoresistant cell-derived exosomes were able to change the chemo-response of chemosensitive recipient cells via transportation of lncRNAs. It has been shown that lncRNA LINC00667 level was significantly elevated in breast cancer tissues. Therefore, we explored whether LINC00667 level is increased in TXT-resistant TNBC cell-derived exosomes. In addition, whether exosomal LINC00667 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…They reviewed many miRNAs, circRNAs and lncRNAs that have implications on chemoresistance in TNBC and hypothesized that ncRNA profiling will be a viable means of selecting a chemotherapy that is likely to garner a response. Examples in the works of literature of ceRNAs that affect the response to chemotherapies include circ_0001667, conferring Adriamycin resistance; LINC00667, conferring docetaxel resistance; BORG, conferring doxorubicin resistance; UBAP, HCP5 and DLX6-AS1, conferring cisplatin resistance; and FTH1P3 and H19, conferring paclitaxel resistance ( Table 2 ) [ 50 , 51 , 66 , 67 , 68 , 69 , 70 , 71 ]. Given the complicated mechanisms of chemoresistance with many effector proteins playing a role, targeting key ceRNA regulatory networks to cover multiple mechanisms or as more reliable markers that are based on a greater number of functional factors may be promising.…”
Section: Significance Of Cernets Alterations In Tnbcmentioning
confidence: 99%
“…They reviewed many miRNAs, circRNAs and lncRNAs that have implications on chemoresistance in TNBC and hypothesized that ncRNA profiling will be a viable means of selecting a chemotherapy that is likely to garner a response. Examples in the works of literature of ceRNAs that affect the response to chemotherapies include circ_0001667, conferring Adriamycin resistance; LINC00667, conferring docetaxel resistance; BORG, conferring doxorubicin resistance; UBAP, HCP5 and DLX6-AS1, conferring cisplatin resistance; and FTH1P3 and H19, conferring paclitaxel resistance ( Table 2 ) [ 50 , 51 , 66 , 67 , 68 , 69 , 70 , 71 ]. Given the complicated mechanisms of chemoresistance with many effector proteins playing a role, targeting key ceRNA regulatory networks to cover multiple mechanisms or as more reliable markers that are based on a greater number of functional factors may be promising.…”
Section: Significance Of Cernets Alterations In Tnbcmentioning
confidence: 99%
“…Similarly, the study found that the expression level of LINC00667 was significantly higher in docetaxel-resistant TNBC cell-derived exosomes than in docetaxel-sensitive TNBC cell-derived exosomes. Exosomal LINC00667 was found to promote the resistance of TNBC cells to docetaxel by regulating the miR-200b-3p/Bcl-2 axis [159]. Additionally, in breast cancer, LINC00461 can act as a ceRNA by directly interacting with miR-411-5p and promotes docetaxel resistance by acting as a sponge for miR-411-5p molecules [171].…”
Section: Lncrnas and Docetaxel Resistance In Breast Cancermentioning
confidence: 99%